2015
DOI: 10.1063/1.4917300
|View full text |Cite
|
Sign up to set email alerts
|

Addressable multi-nozzle electrohydrodynamic jet printing with high consistency by multi-level voltage method

Abstract: It is critical and challenging to achieve the individual jetting ability and high consistency in multi-nozzle electrohydrodynamic jet printing (E-jet printing). We proposed multi-level voltage method (MVM) to implement the addressable E-jet printing using multiple parallel nozzles with high consistency. The fabricated multi-nozzle printhead for MVM consists of three parts: PMMA holder, stainless steel capillaries (27G, outer diameter 400 μm) and FR-4 extractor layer. The key of MVM is to control the maximum me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 33 publications
0
22
0
Order By: Relevance
“…[ 84 ] In any such scheme, electrostatic interference between the individual nozzles must be considered, as established from previous studies of electrohydrodynamic ejection of droplets from arrays of large scale nozzles. [85][86][87][88] The small sizes of nozzles associated with high resolution e-jet printing demand a re-consideration of the electrostatics. Experiments indicated that simultaneous printing from 3 different nozzles with inner diameters of 2 µm can be performed with negligible cross-talk effects when the nozzles are separated www.small-journal.com by more than 80 µm.…”
Section: Modifi Cations To the Electrohydrodynamic Jet Printermentioning
confidence: 99%
“…[ 84 ] In any such scheme, electrostatic interference between the individual nozzles must be considered, as established from previous studies of electrohydrodynamic ejection of droplets from arrays of large scale nozzles. [85][86][87][88] The small sizes of nozzles associated with high resolution e-jet printing demand a re-consideration of the electrostatics. Experiments indicated that simultaneous printing from 3 different nozzles with inner diameters of 2 µm can be performed with negligible cross-talk effects when the nozzles are separated www.small-journal.com by more than 80 µm.…”
Section: Modifi Cations To the Electrohydrodynamic Jet Printermentioning
confidence: 99%
“…This printing technique can be used to produce three‐dimensional structures and high‐resolution patterning, because the small droplets dry very quickly during or immediately after the printing process. Although e‐jet printing typically uses a single nozzle, several studies have developed e‐jet printing that uses multiple nozzles to improve the throughput of the printing technology . The first study of high‐resolution TFTs using e‐jet printing was reported by Rogers and coworkers in 2007 .…”
Section: High‐resolution Printing Technologiesmentioning
confidence: 99%
“…“Auxiliary electrodes,” “Near‐field electrospinning,” “Light‐emitting coaxial nanofibers,” Copyright, respectively, 2003, 2006, 2012, American Chemical Society. “Mathematical model of whipping,” “Silicon based addressable nozzles,” “High consistency by multi‐level voltage,” Copyright, respectively, 2000, 2008, 2015, AIP Publishing. “Rotatable disc collectors,” “Computational model of NFES,” Copyright, 2001, 2010, IOP Publishing.…”
Section: Evolution Of Ehd Direct‐writingmentioning
confidence: 99%
“…Now, the EHD direct‐writing is able to fabricate not only 2D micro/nanopatterns but also 3D frameworks, through either solution or melt‐based electrospinning . When multi‐nozzle is adopted, much more efficient system can be achieved compared to the inkjet printing system . These achievements will no doubt advance the development of EHD direct‐writing in flexible electronics manufacturing.…”
Section: Evolution Of Ehd Direct‐writingmentioning
confidence: 99%